Randomized Controlled Trial to Assess the ACE Program for Rehabilitation in Patients with Hearing Loss. (23rd August 2013) - Cardemil, Felipe; Esquivel, Patricia; Barría, Tamara; Aguayo, Lorena; Fuente, Adrian; Espejo, Maritza R.
Abstract : Objectives: Implement a standardized counselling program in elderly patients with hearing loss users of hearing aids and evaluate its utility in terms of adherence to hearing aids. Methods: A randomized clinical trial was carried out during the period from October 2011 to August 2012, with a follow‐up of 6 months, approved by the hospital ethics committee. Patients 65 years and older with hearing loss diagnosed by pure tone audiometry who were patients from the National Public Health Service were included. The intervention used was a rehabilitation program called Active Communication Education (ACE), designed in Australia in 2007, which aims to improve rehabilitation of hearing aids users. To assess adherence, the International Outcome Inventory for Hearing Aids scale was used. Results: One hundred and eighty patients were evaluated, corresponding to 90 control and 90 rehabilitated patients. The overall adherence of hearing aids use was 78%. There was no difference in sex, age, and audiometric variable groups. The average daily hours of use in the control group were 6.9 hours, compared with 9.6 hours in the intervention group (P < 0.0001). There was a significant association between the intervention and the use of the hearing aid, with a greater proportion of patients who used more than 8 hours per week in the intervention group (66.6% vs 33.3%, P < 0.001). Conclusions: The intervention implemented has shown excellent preliminary results in terms of time of use of the hearing aid. It would be useful to include this intervention in the hearing loss national public policy.